Esophageal cancer surgery: review of complications and their management. Issue 1 (15th September 2020) - Chevallay, Mickael; Jung, Minoa; Chon, Seung‐Hun; Takeda, Flavio Roberto; Akiyama, Junichi; Mönig, Stefan
Abstract: Esophagectomy, even with the progress in surgical technique and perioperative management, is a highly specialized surgery, associated with a high rate of complications. Early recognition and adequate treatment should be a standard of care for the most common postoperative complications: anastomotic leakage, pneumonia, atrial fibrillation, chylothorax, and recurrent laryngeal nerve palsy. Recent progress in endoscopy with vacuum and stent placement, or in radiology with embolization, has changed the management of these complications. The success of nonoperative treatments should be frequently reassessed and reoperation must be proposed in case of failure. We have summarized the clinical signs, diagnostic process, and management of the frequent complications after esophagectomy for esophageal cancer. Abstract : Esophagectomy, even with the progress in surgical technique and perioperative management, is a highly specialized surgery, associated with a high rate of complications. Early recognition and adequate treatment should be a standard of care for the most common postoperative complications. We have summarized the clinical signs, diagnostic process, and management of these frequent complications after esophagectomy for esophageal cancer.